Methods of formation of system of the automated land use planning - T V Papaskiri (RUDN Journal of Agronomy and Animal Industries, 2015)
The article discusses the concept of the automated land use planning (SASPR - Land CAD system). Methodical approaches, structure, and building SASPR and its infor-mational, organizational, and functional software. And formulate the General theoretical principles and methodological principles for the creation of SASPR. In SASPR must be made uniform system solutions, which fully uses the resources and potential sources of im-provement of quality control and improvement of the organization of agricultural production and labor.